Evolutionary Game and Numerical Simulation of Cultivated Land Protection Policies Implementation in China. (26th November 2021) - Lu, Xinhai; Zhang, Yanwei; Zou, Yucheng
Abstract : The effective implementation of cultivated land protection policies (CLPP) has important practical significance for improving China's food security and ecological security. The central government, local governments, and farmers have mutually restricted and influencing interest relations. At the same time, the codes of behavior of multistakeholders also affect the implementation of CLPP in the social system. Therefore, this article discusses the behavioral tendencies and game relationships of relevant stakeholders in the implementation of CLPP from the perspective of evolutionary games and portrays a cognitive decision-making process closer to reality. Finally, numerical simulation reveals the key variables that affect the stability strategy. Results show the following: (1) As the main body of system supply, the central government should reconstruct the political achievement evaluation system and improve the status of the effective implementation of cultivated protection policies in the political achievement evaluation of local governments. (2) The central government should increase incentives for local governments to implement CLPP and increase penalties for violations to improve the effectiveness of policy implementation. (3) To optimize the actual implementation of CLPP, increasing awareness of farmers' rights protection, reducing rights protection costs of farmers, and increasing the constraints on the flexible implementation of CLPP are necessary.